A critical content analysis of English textbook for senior high school students in Indonesia - Urip Sulistiyo; Retno Wulan; Tubagus Zam Zam Al Arif; Dony Efriza; Kaspul Anwar (Universitas Syiah Kuala, 2021)
Driven by sparse investigations on cultural content in a textbook in English as a foreign language context, this study aims to analyze the cultural information embedded in an English textbook for senior high school students in Indonesia. A critical content analysis was employed to analyze the textbook entitled “Pathway to English for SMA/MA Grade XI” in compliance with the cultural information cores from Adaskou et al. (1990). The findings showed that the textbook contains four main topics of cultural information infused in 14 reading texts, 20 pictures, 30 recordings, and seven cultural awareness texts. The reading texts provide equal information related to target culture (i.e., the culture belongs to English speaking countries) and local culture, but the pictures, recordings, and cultural awareness topics tend to inform the target culture information. Furthermore, the researchers found several weaknesses in the reading texts and pictures where the information provided was too general that they neither contain cultural information nor relevant to other information in the textbook. Meanwhile, all pictures were in white and black with less detail provided. The results suggested that teachers should adapt and balance the cultural information in the textbook with their local cultures or norms by finding other materials from various sources.